(untitled) (Research, Society and Development, 2022)
With the COVID-19 pandemic, there was an increase in the stressful load of professionals working in health units, causing them occupational stress and emotional, physical and behavioral changes. In this study, the objective was to describe the emotional aspects related to occupational risks in face of the new Coronavirus that can affect the health conditions of professionals working during the pandemic, in the city of Rondonópolis-MT. This is a study with a quantitative, field and descriptive approach, carried out with 69 professionals who have been working in the Sentinel Units. Data were organized in electronic spreadsheets of the Microsoft Office Excel® program, calculated absolute and relative frequencies, analyzed using descriptive statistics. These were mostly female, being 66 (95.65%); aged <35 years 27 (39, 13%); 41 (59.42%) with a marital relationship and 58 (84.06%) children. Regarding the working conditions of the participating professionals, the majority, 43 (62.32%) reported feeling insecure, even though the majority responded that the working conditions were sufficient and good, 56 (79.71%) and 51 (73.91%) perceived some change in the emotional and/or physical and/or behavioral scope. The most reported emotional changes were anxiety, fear and irritability, with 36, 23 and 11 responses, respectively. It is inferred that the stress suffered by these professionals led them to have emotional, physical and behavioral changes that result in the risk of both mental disorders and psychosomatic illnesses and physical illnesses; especially if they do not have or do not seek medical and psychological assistance.